PEMETAAN INDUSTRI PARIWISATA - Robertus Tang Herman (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
The purpose of this research is to provide conceptual and infrastructur tools for Dinas Pariwisata to improve their capabilities for evaluating business performance based on market responsiveness. Capturing market responsiveness is the initial research to make industry mapping. Research steps are start with secondary research to built data classification system. The second is primary research by collecting the data from market research. Data sources for secondary data was collected from Dinas Pariwisata DKI, while the primary data was collected from survey method using quitionaires addressed to the whole market. Then, analyze the data colleted with cluster analysis to develop the mapping. The result of cluster analysis will distinguish the potential market based on their responses to the industry classification, make the classification system, find the gaps and how important are they, and the another issue related to the role of the mapping system. So, this mapping system will help Dinas Pariwisata to improve capabilities and the business performance based on the market responsiveness and, who is the potential market for each specific classification, know whats their needs, wants and demand from those classifications. This research contribution can be used to give the recommendation to Dinas Pariwisata to deliver what is market needs for entire tourism place based on this classification resulting, develop the market growth estimation and for the long term is to improve the economic and market growth.